'Kiriman ekspres' a study of the prospects and problems / Badroolhisham Mohd. Salleh - Mohd. Salleh, Badroolhisham (1989)
Nowadays there are many agencies getting involved in parcel industry. Within the nation, as a result of rapid growth of the number of operators, the market tend to expand. Each operators try to control a portion of market, the same thing goes for Malayan Railway. Malayan Railway is only interested in transporting passenger and freight. In fact these two- sector produced the highest revenue for Malayan Railway. Actually the idea of carrying parcel by Malayan Railway was introduced during the colonial days, and Malayan Railway monopolized the market as it is the only operator for parcel. Recently, new parcel agencies were established and open up the market share for more challenging industry. Eventually, Malayan Railway has lost its market share to these agencies because these agencies offered better services, for example, a desk-to-desk service. Regarding this phenomena, Malayan Railway started to realize that the. parcel service need an identity in order to be established. So the name 'Kiriman Ekspres' has, been chosen. This is to differentiate this service from others.